Do environmental services buyers prefer differentiated rates? a case study from the Colombian Andes - Moreno Sánchez, R.P.; Maldonado, J.H.; Wunder, Sven; Borda, C.A. (Universidad de los Andes, 2009)
Flat user fees in payment for environmental services (PES) schemes promote administrative ease, and are sometimes perceived as egalitarian. However, when environmental service (ES) buyers are heterogeneous in their income and water consumption levels, this may not be optimal, as total payments become too low and services are under-supplied. This paper identifies ES buyer preferences and estimates their willingness to pay (WTP) differentiated fees in an ongoing PES initiative in an Andean watershed in Colombia. Small, flat user payments have recently been introduced to implement incipient watershed protection upstream. Environmental service users fall into two highly heterogeneous categories: smallholder peasants and owners of recreational houses. We performed a contingent valuation analysis in a representative stratified sample of 218 user households. For improved water services, ES buyers on average were willing to pay a monthly US$1 premium over current flat PES rates. Owners of recreational houses were willing to pay about US$1.50 more; smallholders only US$0.5. 85% of ES buyers also agree to pay differentiated fees. Of these, 41% would prefer fees differentiated by water consumption, 23% by household income, 30% criteria combination, and 6% by other criteria. Spatial variables, such as distance to the water distribution point and to the town center, importantly influenced WTP. The results may help designing users-driven PES schemes in accordance with efficiency and equity objectives.